Comparison of waist-to-hip ratio and other obesity indices as predictors of cardiovascular disease risk in people with type-2 diabetes: A prospective cohort study from ADVANCE - Czernichow, S.; Kengne, A.; Huxley, Rachel; Batty, G.; De Galan, B.; Grobbee, D.; Pillai, A.; Zoungas, S.; Marre, M.; Woodward, M.; Neal, B.; Chalmers, J. (2011)
Aims: The aim of this study was to compare the strength of associations and discrimination capability of body mass index (BMI), waist circumference (WC) and waist-to-hip ratio (WHR) with cardiovascular disease risk in individuals with type-2 diabetes. Methods and results: Eleven thousand, one hundred and forty men and women were followed for a mean of 4.8 years. The Cox proportional hazard models were used to compute the hazard ratios and 95% confidence intervals (95% CI) for one standard deviation (SD) increase in baseline BMI (SD: 5kg/m2), WC (SD: 13cm) and WHR (SD: 0.08) with cardiovascular disease risk. After adjustment, hazard ratio (95% CI) for WC were 1.10 (1.03-1.18) for cardiovascular events, 1.13 (1.03-1.24) for coronary events, and 1.08 (0.98-1.19) for cardiovascular deaths. Estimates for WHR were 1.12 (1.05-1.19), 1.17 (1.08-1.28) and 1.19 (1.09-1.31). BMI was not related to any of these outcomes. Although the receiver operating characteristic curve could not differentiate between anthropometric variables (P values = 0.24), the relative integrated discrimination improvement statistic showed an enhancement in the discrimination capabilities of models using WHR for cardiovascular outcomes, except for cerebrovascular events. Conclusion: Strengths of associations and discrimination statistics suggested that WHR was the best predictor of cardiovascular events and mortality in patients with type-2 diabetes and BMI the worst. © The European Society of Cardiology 2011.